Characteristics of roasting arabica and robusta coffee beans with rotary cylinder tube roast machine with electric heat source. Issue 1 (1st December 2022) - Syafriandi,; Lubis, A; Fadhil, R; Paramida, O
Abstract: Arabica and Robusta coffee beans have physical differences in general. In the process of roasting coffee beans with different physical forms, it is possible that there will be differences in the roasting temperature and water content of the beans after the roasting process. Arabica and Robusta coffee beans have physical differences in general. In the process of roasting coffee beans with different physical forms, it is possible that there will be differences in the roasting temperature and water content of the beans after the roasting process. In brewing coffee, it can also be affected by the roasting process. There are several factors that need to be considered in the roasting coffea bean namely early moisture of coffea beans, temperature in the roaster and the time it takes for the coffee beans to ripen as desired. The use of heat energy to get a specific aroma and taste in coffee beans is very necessary. The objective of the research is to determine how the criteria of the roast of Arabica coffea beans and Robusta coffee beans using cylindrical roaster rotates with electrical energy as its heat source. The results obtained at the treatment temperature of 205°C using a rotating cylinder tube coffee roaster using an electric heat source takes 78 minutes to reach coffee maturity with a dark roast level of maturity. Analysis of the color of coffee beans after roasting, it was found that Arabica coffee and Robusta coffee were more dominant, showing on the color track-60 with the Agtron Color Classification System scale, where the initial moisture content of dry robusta beans is 12.50% reduced to 3.66% after roasting, while the initial moisture content of arabica beans is 12.36% reduced to 3.54%.